ОПЫТ ЭСТОНИИ В РАЗВИТИИ ЭЛЕКТРОННОГО ПРАВИТЕЛЬСТВА (E-GOVERNMENT) КАЗАХСТАНА - A. Sh. Suleimenova (Экономика: стратегия и практика)
The article analyzes the achievements and development of Estonia thanks to the E-Estonia program launched in 1997. Also, the main problems of e-government of Kazakhstan - e-government, which, in principle, uses the experience of Estonia, are discussed. Considering that Estonia was also part of the Soviet Union, for Kazakhstan their experience is doubly interesting.The article also discusses the shortcomings and problems of the e-government of Kazakhstan - e-gov.kz and gives suggestions and recommendations for improving this system.